Cytokine Treatment of Macrophage Suppression of T Cell Activation - Silberman, Daniel (2009)
High Mφ:T cell ratios suppress the immune response to the retroviral superantigen Mls by IFNγ-triggered production of the arg- and trp-consuming enzymes iNOS and IDO. Attempts to reverse suppression by treatment with pro-inflammatory cytokines revealed that IL-6 improved the T cell response to Mls and the pro-hematopoietic cyokines IL-3 and GM-CSF increased suppression. GM-CSF treatment increased Mφ expression of CD80, a ligand for the immune suppressive B7H1 and CTLA-4 receptors. These results illustrate potential strategies for reversing the suppression of cell-mediated immunity characteristic of the high Mφ:T cell ratios found in many tumors.